The Influence of Electronic Personalization on Performance of Three to Five-Star Hotels in Kenya - Gioko, Sylvia Mukenyi; Mukulu, Elegwa; Oloko, Margaret (European Scientific Journal, ESJ, 2021)
Electronic Personalization plays a vital role in the growth and development of the hotel industry, whether in a developed or a developing economy. The hotel industry in Kenya has grown enormously since the year 2000, and despite this growth, the hotel industry in Kenya has experienced slow growth compared to other countries. Electronic Personalization has been identified as an electronic customer relationship management strategy that has had a significant impact on hotel performance. The aim of this study is therefore to seek the influence of Electronic Personalization on the performance of Three to Five-Star Hotels in Kenya. The study adopted a descriptive design for the research. In addition, a quantitative and qualitative research approach was utilized. The target population for the study was one hundred and twelve Three to Five-Star Hotels in Kenya. The study examined one hundred and twelve Three to Five-Star Hotels because they represent the major market share of Kenya’s hotel industry. A survey was conducted on the target population. Simple Regression was utilized to draw inference from the data collected. Descriptive findings revealed a mean of 4.524 with a standard deviation of 0.5654 for electronic personalization. In addition, findings revealed an R square value of 0.366 between Electronic Personalization and performance. This suggests that Electronic Personalization influences the performance of Three to Five-Star Hotels. Consequently, hotel managers should develop and implement effective Electronic Personalization strategies in their hotel’s operations. For instance, they can electronically personalize their hotel information by assigning the right marketing effort to the right customer, hence increasing customer buying behaviour which shall in turn increase performance.